Math’s Anxiety: Classroom Culture as a Causing Factor - Gnawali, Yagya Prasad (Humanities and Social Sciences Journal, 2023)
The aim of this study is to find out the basis of math’s anxiety: classroom culture as a causing factor. A quantitative research strategy based on the positivist paradigm was used. The main objective of this study was to identify the causes of math’s anxiety over the classroom circumstances. A random sample of 190 respondents in the tenth grade—95 boys and 95 girls—was chosen from among the students enrolled in the 19 community schools in the Kathmandu district. A self-made questionnaire with 35 statements and five-point Likert-type response options were used to collect data. Expert feedback was used to confirm the validity of the self-developed questionnaire, and reliability was determined using Cronbach's alpha, which found out to be 0.82 using Delphi methodology. In accordance with the loading components, I had all four components prepared. It was concluded that, overcrowded classroom, attitude towards mathematics, pessimistic past experience and comparative culture are the main causing factors of math’s anxiety.